POLLUTION LOAD INTO DA NANG BAY - Sinh, Le Xuan; Nam, Le Van (Vietnam Journal of Marine Science and Technology, 2015)
Based on the current statistic data and socio-economic development planning to 2025 of Da Nang city, land-based pollution load from development activities has been calculated by using the rapid assessment of water pollution sources. The obtained results showed that each year development activities in Da Nang city discharged into Da Nang bay about 42 thousand tons of COD; 23 thousand tons of BOD5; 9 thousand tons of total nitrogen; 3 thousand tons of total phosphorus and 140 thousand tons of TSS (development activities including living activities, aquaculture, industry, farming and soil washing). Until 2025, these pollution loads will increase by 1.3 - 1.7 times. The main pollution sources are from domestic activities (residents and tourists) and livestock farming. Therefore, treatment of liquid and solid wastes from those sources is very necessary to mitigate the amount of waste into the bay.